A combination of receptor mediated transcytosis and photothermal effect promotes BBB permeability and the treatment of meningitis using itraconazole. Issue 46 (24th November 2020) - Zhang, Shan-Shan; Asghar, Sajid; Ye, Jun-Xiu; Lin, Ling; Ping, Qi-Neng; Chen, Zhi-Peng; Shao, Feng; Xiao, Yan-Yu
Abstract : Fungal infections of the central nervous system (CNS) may lead to life-threatening meningitis. Abstract : Fungal infections of the central nervous system (CNS) may lead to life-threatening meningitis. Itraconazole (ITZ) is an effective antifungal agent that can be used to treat various fungal infections; however, its poor solubility along with poor permeability of the blood–brain barrier (BBB) prevents it from treating meningitis. Receptor mediated transcytosis (RMT) shows modest efficacy in BBB crossing, while affinity and saturability of interactions between ligands and receptors account for the limited efficacy of RMT in crossing the BBB. Mild hyperthermia could temporarily disrupt the BBB to increase its permeability. Therefore, we speculated that the combination of mild hyperthermia with RMT could potentially increase BBB permeability of ITZ leading to improved efficacy in fungal meningitis. Here, we have constructed for the first time, apolipoprotein E (Apo E) mimicked peptide COG1410 modified polydopamine (PDA)-coated bovine serum albumin nanoparticles (ApoE-PDA@ITZ-NPs). Different levels of COG1410-modified NPs were prepared and characterized. ApoE-PDA@ITZ-NPs have a superior photothermal effect under 808 nm light irradiation and exhibited favorable plasma stability and photothermal stability. Moreover, the cellular uptake of nanoparticles increased with an increase in COG1410. H-ApoE-PDA@ITZ-NPs increased cellular uptake and in vitro BBB permeability by 4.2-fold and 4.8-fold, respectively, compared to the ITZ-NPs. Live imaging implied that H-ApoE-PDA@ITZ-NPs could significantly increase the distribution of ITZ in the brain under 808 nm light irradiation. Histopathological analysis of periodic acid-Schiff-stained brain sections of the H-ApoE-PDA@ITZ-NP treated C. albicans meningitis model indicated that H-ApoE-PDA@ITZ-NPs showed superior antifungal activity after 808 nm light irradiation. Hence, we report ApoE-PDA@ITZ-NPs in tandem with 808 nm irradiation as a novel strategy of RMT combination with a photothermal effect in enhancing BBB permeability to facilitate drug accumulation in the brain region and enhance the therapeutic efficacy of ITZ in meningitis.